HUBUNGAN KEPUASAN BELAJAR DENGAN MOTIVASI BELAJAR WARGA BELAJAR KESETARAAN PAKET C DI SPNF SKB KABUPATEN GOWA - Munarti, Mifra; Marzuki, Kartini; Asri, Muhammad (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2025)
This research is a quantitative research using a survey method which aims to determine the relationship between learning satisfaction and the learning motivation of residents studying Package C equality at SPNF SKB Gowa Regency. The independent variable in this research is learning satisfaction, while the dependent variable in this research is learning motivation. The population in this study was 133 residents studying the Gowa Regency SPNF SKB Package C equality program. Sampling was carried out using a stratified random sampling technique which was then determined as many as 57 people. The data collection method was carried out using a research instrument in the form of a questionnaire. The data analysis technique used is product moment correlation analysis. The results of this research show that there is a relationship between learning satisfaction and the learning motivation of residents studying equality Package C at SPNF SKB Gowa Regency. This is known by carrying out a product moment correlation analysis test which shows that the correlation coefficient value is 0.534 with a significance value of 0.000 <0.05, so Ha is accepted and Ho is rejected, which means there is a real (significant) correlation between the Learning Satisfaction (X) variable and Learning Motivation (Y). Thus, based on the correlative coefficient interpretation table, the level of correlation between the learning satisfaction variable (X) and the learning motivation variable (Y), namely 0.534, is at a moderate level of relationship.